2021
DOI: 10.1021/acsaem.1c01465
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Generated InOx/ZrO2 Catalysts for CO2 Hydrogenation: Role of In Situ Fragmentation and Ripening Control

Abstract: It is desirable to reduce the reliance on fossil fuels and to develop alternative methods to yield valuable chemicals. CO2 hydrogenation to methanol is a promising approach, where In2O3/ZrO2 catalysts have attracted increasing attention due to their high selectivity and stability. However, the activity of indium-based catalysts is very susceptible to the preparation method, which is typically wet impregnation. Here, we explore a laser-based synthesis route to prepare InO x /ZrO2 catalysts of varying indium siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…The combination of In 2 O 3 and ZrO 2 as a support achieved a synergistic effect at the interface between oxygen vacancy defects of the oxides [17] . Adjusting the right particle size and morphology control are key factors for preparing Indium‐based catalysts with high activity [18] . The ZrO 2 carrier plays a crucial role in preventing the sintering of In 2 O 3 , thus ensuring long‐time‐stability of the catalyst.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of In 2 O 3 and ZrO 2 as a support achieved a synergistic effect at the interface between oxygen vacancy defects of the oxides [17] . Adjusting the right particle size and morphology control are key factors for preparing Indium‐based catalysts with high activity [18] . The ZrO 2 carrier plays a crucial role in preventing the sintering of In 2 O 3 , thus ensuring long‐time‐stability of the catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…[17] Adjusting the right particle size and morphology control are key factors for preparing Indium-based catalysts with high activity. [18] The ZrO 2 carrier plays a crucial role in preventing the sintering of In 2 O 3 , thus ensuring long-time-stability of the catalyst. According to proposed mechanisms, the oxygen vacancy filled after methanol desorption is regenerated through its hydrogenation by water formation.…”
Section: Introductionmentioning
confidence: 99%
“…22 Nano-sized In 2 O 3 particles can be generated via laser ablation and deployed on ZrO 2 surfaces to tune the microstructure of the catalyst and to adjust the catalyst activity as well. 23 In industrial methanol synthesis, fixed-bed reactors are used. For example, Lurgi's MegaMethanol process uses pressures between 50 and 100 bar and reaction temperatures between 200 and 300 °C.…”
Section: F H Co 2hmentioning
confidence: 99%
“…The integration of noble metals such as Pd and Ru, as well as non-noble metals like Ni, proved to further improve the catalytic activity. ,, The resulting hydrogen spillover effect leads to higher hydrogen availability on the catalyst surface wherein only a small amount of metal loading can boost the catalytic activity significantly . Nano-sized In 2 O 3 particles can be generated via laser ablation and deployed on ZrO 2 surfaces to tune the microstructure of the catalyst and to adjust the catalyst activity as well …”
Section: Introductionmentioning
confidence: 99%
“…Compared with the traditional Cu/ ZnO/Al 2 O 3 catalyst, In 2 O 3 catalysts exhibit excellent methanol selectivity in CO 2 hydrogenation to CH 3 OH. [18][19][20] It was found that the reactivity and CH 3 OH selectivity can be improved by doping metal oxides or supporting metal nanoparticles on In 2 O 3 . Martin et al obtained high activity using ZrO 2 loaded In 2 O 3 , with the methanol selectivity being close to 100%.…”
Section: Introductionmentioning
confidence: 99%